Review on the Management of Female Urinary Incontinence and Anterior Vaginal Prolapse - Ronscardy F. Mondesir; Angelica Gousse; Daniel A. Boaretto; Daniel Ajabshir; Angelo Gousse (Société Internationale d’Urologie Journal)
Objectives: We aimed to evaluate management strategies for female urinary incontinence, specifically stress urinary incontinence (SUI), and anterior vaginal prolapse (pelvic organ prolapse, POP), emphasizing diagnostic methods, treatment options, and factors influencing surgical outcomes. Methods: We conducted a thorough literature review examining diagnostic tools, including physical examinations, urodynamic testing, and pessary evaluations, alongside treatment options for SUI and POP. Both surgical interventions, such as mid-urethral sling placement and anterior colporrhaphy, and non-surgical methods, including pelvic floor exercises, were analyzed. This review assesses these approaches’ efficacy, complications, and outcomes, incorporating current clinical guidelines and evidence-based practices. Results: Evidence indicates that SUI frequently coexists with POP, with a notable proportion of cases being occult until a prolapse is reduced. Diagnostic methods such as pessary testing and urodynamic evaluations are essential in identifying masked SUI, though their predictive accuracy varies. Surgical techniques such as using mid-urethral slings are highly effective but pose risks, including voiding dysfunction and lower urinary tract injury. Long-term data emphasize the need for personalized treatment strategies, with combined procedures showing superior outcomes for the concurrent management of POP and SUI in select cases. Conclusions: Effective management of SUI and POP requires a personalized approach, factoring in the severity of a prolapse and the likelihood of postoperative incontinence. While conservative treatments are practical initial options, surgical solutions, such as mid-urethral slings and apical suspension procedures, offer robust, lasting results for advanced cases. Preoperative diagnostics, collaborative decision-making, and tailored treatment plans are essential to optimize success and minimize complications. Future research should prioritize enhancing diagnostic precision and refining surgical methods to further advance patient care.